The comparative recovery performance of anion exchange and dye-ligand fluidised bed adsorption of G3PDH from unclarified yeast extract - Ling, Tau Chuan; Lyddiatt, Andrew (Malaysian Society for Molecular Biology and Biotechnology, 2005)
The comparative recovery performance of anion exchange and dye ligand fluidised bed adsorption of intracellular enzyme, glyceraldehydes 3-phosphate dehydrogenase (G3PDH) from unclarified disrupted yeast has been undertaken. The commercially available anion exchanger, Streamline QXL and the kiesleguhr-agarose composite adsorbent, Microsorb K6AX derived with dye-ligand (Cibaron Blue 3GA) were employed in fluidized bed experiments. The adsorbents were evaluated in respect of recovery performance in terms of yield, purity and enzyme specific activity.